Analysis of water quality in natural attractions in the region of Santo Antônio do Rio Abaixo (MG) (Research, Society and Development, 2018)
Tourism is an economic activity that uses the peculiar aspects of a region, such as nature, history, culture and geology. In this way, this work aimed to characterize the water quality quality indices of the tourist attractions Limão Well, Tabuleiro Beach, Benedito Martins Leite Seaside Resort, Angico, Baía, Chuvisco and Cristal waterfalls, located in the municipality of Santo Antônio of Rio Below (MG). Six samples were collected between September 2016 and May 2017, and the Balneability Index (IB), Trophic State Index (EIT) and Water Quality Index (IQA) were analyzed. Considering the IB, it was verified results classified in the "excellent" and "very good" classification of the Resolution of the National Environmental Council (CONAMA) nº 274/2000, except for the Angico Waterfall, given the discharge of sewage near this. On the other hand, the IQA presented results in the "medium" to "good" ranges, according to the standard of the Mining Institute of Water Management. However, it is important to emphasize that the rainy season influenced negatively the results of these indices, given the surface runoff. The results obtained through the EIT allowed the classification of waters as ultraoligotrophic, indicating insignificant concentrations of nutrients. Thus, this work can contribute to the planning of tourism in the municipality, collaborating with the generation of income and improvement of the quality of life of the local population.